Corporate philanthropy at the crossroads - Burlingame, Dwight; Young, Dennis R., 1943- (Philanthropic studies., 1996)
Corporate philanthropy is at a crossroads, moving from a focus on "doing the right thing" for the community to one that emphasizes the bottom line of the corporation. This new corporate landscape presents some important challenges for the nonprofit sector. Corporate Philanthropy at the Crossroads looks at current practices, trends, and issues for corporate philanthropy and frames a productive research agenda based on the needs of practitioners. Here is a useful reference for fundraisers as they implement their strategic plans for the future. Indispensable reading for academics with an interest in corporate philanthropy.